The parsec-scale structure of jet-driven H I out ows in radio galaxies. Issue Volume 14:Issue A30(2018) (August 2018) - Morganti, Raffaella; Schulz, Robert; Nyland, Kristina; Paragi, Zsolt; Oosterloo, Tom; Mahony, Elizabeth; Murthy, Suma
Abstract: Radio jets can play multiple roles in the feedback loop by regulating the accretion of the gas, by enhancing gas turbulence, and by driving gas outflows. Numerical simulations are beginning to make detailed predictions about these processes. Using high resolution VLBI observations we test these predictions by studying how radio jets of different power and in different phases of evolution affect the properties and kinematics of the surrounding H I gas. Consistent with predictions, we find that young (or recently restarted) radio jets have stronger impact as shown by the presence of H I outflows. The outflowing medium is clumpy with clouds of with sizes up to a few tens of pc and mass ∼ 10 4 M ȯ ) already in the region close to the nucleus (< 100 pc), making the jet interact strongly and shock the surrounding gas. We present a case of a low-power jet where, as suggested by the simulations, the injection of energy may produce an increase in the turbulence of the medium instead of an outflow.